Developing a new water–energy–food‐greenhouse gases nexus tool for sustainable agricultural landscape management. (19th October 2022) - Masaeli, Hourieh; Gohari, Alireza; Hasanzadeh Saray, Marzieh; Torabi Haghighi, Ali
Abstract: A new comprehensive water, energy, food, greenhouse gas (WEFG) nexus index was developed to capture the interrelationships between them. A total of 11 indicators were applied to consider the interplay of resources consumption, productivity, economic issues, and carbon emission as one of the most critical issues regarding sustainable agricultural development. The proposed WEFG index was evaluated for crop pattern optimization. The results showed that the WEFG ranged from 0.162 to 0.658, which were calculated respectively for almonds and rice due to their energy consumption and carbon emission levels. The optimal cultivation pattern based on WEFG leads to 11% and 15.8% reductions in water and energy consumption, even with a 2.3% increase in cultivation area. The estimated profit for optimal pattern based on WEFG decreased by 13.67% due to lower cultivation levels of high‐yield crops such as onion and potatoes. However, the optimal cultivation pattern based on the WEFG index has decreased greenhouse gas emissions by 2%, leading to sustainable agricultural management. Therefore, the presented WEFG nexus index can be a practical metric for sustainable planning and management in the agriculture sector.